Associations of maternal emotion regulation with child white matter connectivity in Black American mother–child dyads. Issue 7 (15th July 2022) - Wang, Chenyang; La Barrie, Dominique L.; Powers, Abigail; Stenson, Anais F.; van Rooij, Sanne J. H.; Stevens, Jennifer S.; Jovanovic, Tanja; Bradley, Bekh; McGee, Robin E.; Fani, Negar
Abstract: Parental emotion regulation plays a major role in parent‐child interactions, and in turn, neural plasticity in children, particularly during sensitive developmental periods. However, little is known about how parental emotion dysregulation is associated with variation in children's brain structure, which was the goal of this study. Forty‐five Black American mother–child dyads were recruited from an intergenerational trauma study; emotion regulation in mothers and their children (age 8–13 years) was assessed. Diffusion‐weighted images were collected in children; deterministic tractography was used to reconstruct pathways of relevance to emotion regulation. Metrics of white matter connectivity [fractional anisotropy (FA), mean diffusivity (MD)] were extracted for pathways. Socio‐economic variables were also included in statistical models. Maternal emotion dysregulation was the strongest predictor of child fornix MD ( r  = .35, p  = .001), indicating that more severe emotion dysregulation in mothers corresponded with lower fornix connectivity in children. Maternal impulsivity was a strong predictor of child fornix MD ( r  = .51, p  < .001). Maternal emotion dysregulation may adversely influence connectivity of the child.s fornix, a hippocampal‐striatal pathway implicated in reward processes; these associations remained even after accounting for other socio‐environmental factors. Dysregulated maternal emotions may uniquely impact children's adaptation to trauma/stress by affecting networks that support appetitive processing.